2013
DOI: 10.4314/ejb.v15i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activity of four medicinal plant powders and extracts against Angoumois grain moth, <i>Sitotroga cerealella</i> (Olivier) [Lepidoptera: Gelechidae]

Abstract: Powders and extracts prepared from Capsicum frutescens, Cymbopogon citratus, Moringa oleifera, Anacardium occidentale were tested for their insecticidal potential against Angoumois grain moth, Sitotroga cerealella. The powder of C. frutescens had the highest mortality rate of 100% after 2 days of application at all tested concentrations. The extracts killed all the adult moths introduced at all tested concentrations. The survival of the moth from egg to adult when treated with the plant powders showed signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…This result was in accordance with the findings of Patra et al (2012) and Zeeshan et al (2012) in which methanolic extracts of some plants were found to be effective against Staphylococcus epidermidis than other extracts. The result of this work agreed with the research of Ileke (2013) in which the extracts and powders of different plant were found to reduce adult emergence of S. cerealella infesting wheat grains.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result was in accordance with the findings of Patra et al (2012) and Zeeshan et al (2012) in which methanolic extracts of some plants were found to be effective against Staphylococcus epidermidis than other extracts. The result of this work agreed with the research of Ileke (2013) in which the extracts and powders of different plant were found to reduce adult emergence of S. cerealella infesting wheat grains.…”
Section: Discussionsupporting
confidence: 90%
“…Rice being one of the world staple foods has been infested by a wide range of insect pests in storage including Sitotroga cerealella (Olivier), Sitophilus oryzae L., S. granarius L., Ryzopertha dominica F. , as well as Scirpophaga incertulas and Scirpophaga innotata (Ashamo and Akinnawonu, 2012;Sarwar, 2012;Ileke, 2013). These insects attack paddy rice both on the field and in storage and brought about diminution of this important crop marketability.…”
Section: Introductionmentioning
confidence: 99%